The role of community learning centers program in community literacy development in post revolution Iran - Zolfaghari, Akbar; Sabran, Mohammad Shatar; Zolfaghari, Azam (Faculty of Educational Studies, Universiti Putra Malaysia, 2009)
Globally, previous studies indicate that the number of adolescents with sexual misconduct has steadily increased. In Malaysia, sexual misconduct among adolescents has been an alarming concern to many individuals, non-government organizations (NGO) and government agencies. Adolescents that have been captured for being immorally involved in sexual activities will be placed in the conduct rehabilitation centre. Besides government and non-government organizations, some of these centres were built privately. This study aims to answer the following questions: What are the training offered to the trainee of the centre and their parents? Besides, the financial need, what help can be offered to this centre to help improve the functions of the centre? How do the centers work together with the parents of the trainees in the centre to help prevent relapse cases among the trainees? In this study, 1 private, 1 NGO, and 1 government owned centres participate as the informant. The accounts were gathered through a series of interviews, observation of the researcher and a review of related documents. Preliminary findings indicate that, there are lot of rooms for improvement that can be done to help run the centre. For the privately owned centre, room for improvement and help to be offered is humongous.